Organizational and Social Support in Employee Post-Recovery Adaptation: Evidence from Indonesian Mining - Tidy Natanagari; Jaya Addin Linando (UTSAHA: Journal of Entrepreneurship, 2026)
Employees returning to work following serious illness or workplace injury face complex physical and psychological challenges that extend well beyond the clinical recovery process. Despite growing scholarly interest in organizational support and workplace social support, limited research has examined how these two constructs operate during the post-recovery phase within high-risk industrial settings, particularly in the mining sector. This study investigates the forms of organizational support provided by PT Kaltim Prima Coal and the influence of workplace social support on employee adaptation following recovery. A qualitative phenomenological approach was adopted, and data were collected through semi-structured interviews with six purposively selected employees who participated in the company's Work Rehabilitation Program. Thematic analysis following the six-phase framework of Braun and Clarke was employed, with manual coding conducted through Microsoft Excel. The findings reveal that organizational support operates across three interconnected dimensions: psychosocial recognition, which encompasses employee appreciation and workload adjustment; medical-functional assistance, including clinical consultation and specialist referral; and structural-administrative oversight through continuous HR monitoring. Workplace social support, delivered through supervisory guidance, emotional validation, and peer collaboration, further reduces occupational stress, restores self-confidence, and strengthens work motivation during reintegration. Structured reintegration through the WRP was also perceived as substantially more restorative than conventional sick leave arrangements. Collectively, these findings extend Perceived Organizational Support theory to a previously underexamined population and offer evidence-based implications for occupational rehabilitation policy design in high-risk industrial environments.